Bone marrow amyloid: a comprehensive analysis of 1, 469 samples, including amyloid type, clinical features, and morphologic distribution. (3rd July 2022) - Chiu, April; Dasari, Surendra; Kurtin, Paul J.; Theis, Jason D.; Vrana, Julie A.; Dispenzieri, Angela; Rech, Karen L.; Dao, Linda N.; Howard, Matthew T.; Grogan, Martha; McPhail, Ellen D.
Abstract: Background: Bone marrow biopsy is common in patients suspected of having systemic AL amyloidosis. However, little is known about the incidence, morphology and clinical phenotype of non-AL amyloid types in bone marrow. Methods: We retrospectively identified N = 1469 bone marrow amyloid biopsies typed using a proteomics-based method between 2008–2020. Frequency of amyloid types ( N = 1469), distribution of amyloid deposits ( N = 139), and clinical phenotypes ( N = 355), with particular emphasis on cardiac involvement, were assessed. Results: The amyloid types were: AL ( N = 1172; 79.8%), ATTR ( N = 240; 16.3%), AH ( N = 38; 2.6%), AA ( N = 17; 1.2%), and Aβ2M ( N = 2; 0.1%). Although there were characteristic morphologic features, including periosteal soft tissue and/or vascular involvement in ATTR, interstitial vascular involvement in AA, and variable anatomic compartment involvement in AL, none were pathognomonic. Most patients with both an M-spike and cardiac involvement had AL amyloid in their BM, but in over 10% the amyloid type was ATTR. Compared to AL patients, ATTR patients had higher stage cardiac amyloidosis and lower overall survival, which was mainly due to advanced cardiac stage. Conclusions: ATTR amyloid is common in bone marrow and its morphologic distribution overlaps with AL. Amyloid typing is critical as over 10% of patients with bone marrow amyloid, cardiac amyloidosis, and an M-spike have ATTR amyloidosis.